Water for food systems and nutrition. Food Systems Summit Brief prepared by research partners of the Scientific Group for the Food Systems Summit 2021 - Ringler, Claudia; Agbonlahor, Mure Uhunamure; Baye, Kaleab; Barron, Jennie; Hafeez, Mohsin; Lundqvist, Jan; Meenakshi, J.V.; Mehta, Lyla; Mekonnen, Dawit Kelemework; Rojas Ortuste, Franz; Tankibayeva, Aliya; Uhlenbrook, Stefan (University of Bonn, 2021)
Access to sufficient and clean freshwater is essential for all life. Water is also essential for food system functioning: as a key input into food production, but also in processing and preparation, and as a food itself. Water scarcity and pollution are growing, affecting poorer populations, particularly food producers. Malnutrition levels are also on the rise, and this is closely linked to water scarcity. Achievement of Sustainable Development Goal 2 (SDG 2) and Sustainable Development Goal 6 (SDG 6) are co-dependent. Solutions to jointly improve food systems and water security outcomes that the United Nations Food Security Summit (UNFSS) should consider include: 1) Strengthening efforts to retain water-based ecosystems and their functions; 2) Improving agricultural water management for better diets for all; 3) Reducing water and food losses beyond the farmgate; 4) Coordinating water with nutrition and health interventions; 5) Increasing the environmental sustainability of food systems; 6) Explicitly addressing social inequities in water-nutrition linkages; and 7) Improving data quality and monitoring for water-food system linkages, drawing on innovations in information and communications technology (ICT).